Multiwavelength observations of the γ-ray blazar PKS 0528 in quiescence - Palma, Norman I.; Böttcher, M.; Calle, I. de la; Agudo, I.; Aller, M.; Aller, H.; Bach, U.; Benítez, E.; Buemi, C. S.; Escande, L.; Gómez, J. L.; Gurwell, M. A.; et al. (The astrophysical journal, 2011)
We present multiwavelength observations of the ultraluminous blazar-type radio loud quasar PKS 0528+134 in quiescence during the period 2009 July-December. Four Target-of-Opportunity observations with the XMM-Newton satellite in the 0.2-10 keV range were supplemented with optical observations at the MDM Observatory, radio and optical data from the GLAST-AGILE Support Program of the Whole Earth Blazar Telescope and the Very Long Baseline Array, additional X-ray data from the Rossi X-ray Timing Explorer (2-10 keV) and from Suzaku (0.5-10 keV) as well as γ-ray data from the Fermi Large Area Telescope in the 100 MeV-200 GeV range. In addition, publicly available data from the SMARTS blazar monitoring program and the University of Arizona/Steward Observatory Fermi Support program were included in our analysis. We found no evidence of significant flux or spectral variability in γ-rays and most radio bands. However, significant flux variability on a timescale of several hours was found in the optical regime, accompanied by a weak trend of spectral softening with increasing flux. We suggest that this might be the signature of a contribution of unbeamed emission, possibly from the accretion disk, at the blue end of the optical spectrum. The optical flux is weakly polarized with rapid variations of the degree and direction of polarization, while the polarization of the 43 GHz radio core remains steady, perpendicular to the jet direction. Optical spectropolarimetry of the object in the quiescent state suggests a trend of increasing degree of polarization with increasing wavelength, providing additional evidence for an unpolarized emission component, possibly thermal emission from the accretion disk, contributing toward the blue end of the optical spectrum. Over an extended period of several months, PKS 0528+134 shows moderate (amplitude ≲ 50%) flux variability in the X-rays and most radio frequencies on ∼1-2 week timescales. We constructed four spectral energy distributions (SEDs) corresponding to the times of the XMM-Newton observations. We find that even in the quiescent state, the bolometric luminosity of PKS 0528+134 is dominated by its γ-ray emission. A leptonic single-zone jet model produced acceptable fits to the SEDs with contributions to the high-energy emission from both synchrotron self-Compton radiation and Comptonization of direct accretion disk emission. Fit parameters close to equipartition between the energy densities of the magnetic field and the relativistic electron population were obtained. The moderate variability on long timescales, compared to expected radiative cooling timescales, implies the existence of ongoing particle acceleration, while the observed optical polarization variability seems to point toward a turbulent acceleration process. Turbulent particle acceleration at stationary features along the jet therefore appears to be a viable possibility for the quiescent state of PKS 0528+134.
Gesehen am 14.06.2013